S123 Occupational exposures to wood, metal, and stone in IPF; findings from the idiopathic pulmonary fibrosis job exposures study (IPFJES). (12th November 2019) - Reynolds, C; Sisodia, R; Barber, C; Cullinan, P
Abstract : Introduction and objectives: Case-control studies investigating occupational exposures in idiopathic pulmonary fibrosis (IPF) have found associations with wood, metal, and stone dust. A recent meta-analysis of these studies found pooled odds ratios of 1.7 (1.3–2.2), 2.0 (1.3–3.0), and 1.7 (1.2–2.4) respectively. The majority of studies relied on self-reported exposure histories and used community controls; approaches vulnerable to bias. Our aim was to investigate wood, metal, and stone dust associations by means of a lifetime occupational history, which included details of job tasks, in a hospital based case-control study. Methods: Participants (488 cases, 368 controls; all men) from a UK based multicentre hospital-based case-control study, the idiopathic pulmonary fibrosis job exposures study (IPFJES), were asked to recall details of their occupational history including describing job tasks within each job. They were not asked directly about specific exposures. Participants who described working with wood, metal or stone (or silica) were labelled as exposed and (unadjusted) odds ratios for associations between exposure and IPF were calculated. Results: 45 cases (9%) and 28 controls (8%) were exposed to wood (OR 0.81 p=0.5), 86 cases (18%) and 48 controls (13%) were exposed to metal (OR 1.43 p=0.07), and 23 cases (5%) and 8 controls (2%) were exposed to stone (OR 2.23 p=0.06). Conclusions: Unprompted reports of wood, metal, and stone dust exposure from job task descriptions are not significantly statistically associated with IPF risk in IPFJES. Our exposure measures may lack sensitivity or estimates of association in previous studies may be an artefact of study-design.